Langkawi Island as a tourist friendly destination / Abd Qayyum Abd Jalil - Abd Jalil, Abd Qayyum (2013)
Tourism destination has seen as a combination of products and experience which influencing tourists to travel. Even though there are a lot of studies in various aspects of tourism destination, the evolution of tourist tastes and demands as well as an increasing of travel potential, have called for a tourism destination to be more creative and innovative in offering niche tourism or more importantly, tourist friendly destination. Tourist friendly destination is a concept that provides tourists with satisfaction through connection and maximum use of space, activities, and products without any interference or problems. This study was done in Langkawi Island, the most historical and popular island in Malaysia. Therefore, by using the concept, this empirically study was done to identify whether Langkawi Island fix with all the elements in the tourist friendly destination concept. Using a whole island area as contextual setting, about 302 of domestic tourists were self administered surveyed. Through a series of analyses, the majority of the respondents were agreed that Langkawi Island surely can be stated as a tourist friendly destination. Despite some improvements need to be done, this study showed that Langkawi Island had fulfill almost all of the conditions in the concept. The result also proved that satisfaction level showed by the respondents will lead them to revisit and recommend this island to others.